ANALISIS GRINDLE PADA DANA HIBAH PILWAKOT BANDAR LAMPUNG 2020 - Dinia, Zikriyanti Kurnia; Maryana, Tabah (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The disbursement of the Bandar Lampung Pilwakot Grant Fund in the 2020 Pilkada is currently carried out in a term/stage manner and there are often delays in disbursement. As a result, the implementation of the electoral process was disrupted. This study aims to find out how the implementation of the grant transfer policy in Permendagri Number 54 of 2019 by the Bandar Lampung City Government towards the Bandar Lampung City KPU. This type of research is descriptive qualitative. Sources of data in the form of interviews with informants, library documents, and scientific research results. The results show that the implementation of the grant transfer policy according to the Minister of Home Affairs No. 54 of 2019 at the Bandar Lampung City KPU has not been obeyed by the Bandar Lampung City Government. Namely in the 2020 Bandar Lampung City Election, although there is already a Regulation of the Minister of Home Affairs Number 54 of 2019 in article 16 paragraph (3) regarding the stages of disbursing the regional election budget and this is stated in NPHD Number 10/NPHD/HK/2020 and Number 063/KU .07-SPj/KPU-Kota/I/2020 January 23, 2020. The author recommends that the election budget be evaluated, one of which is changing the source of the Pilkada budget to the State Revenue and Expenditure Budget (APBN).